2015
DOI: 10.1016/j.foodqual.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The green halo: Mechanisms and limits of the eco-label effect

Abstract: a b s t r a c tConsumers believe that ''eco-labeled'' products taste better, which, at least in part, may be an effect of the label. The purpose of the current series of experiments was to examine some mechanisms and limits of this eco-label effect. In Experiment 1, an eco-label effect of similar magnitude was found for taste ratings of both conventional and organic bananas. Experiment 2 showed eco-label effects for a wider range of judgmental dimensions (i.e., health, calories, vitamins/minerals, mental perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
110
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 46 publications
(74 reference statements)
14
110
3
2
Order By: Relevance
“…For example, it is possible that consumers might want to eat more seafood to follow common health claims and therefore over-report the amount of seafood eaten per week. Social desirability bias regarding pro-environmental behavior might also lead to an over-reporting of sustainable seafood consumption behavior [87][88][89]. Hence, experimental replications with actual behaviour as the dependent variable would be a valuable extension of the present research.…”
Section: Limitationsmentioning
confidence: 93%
“…For example, it is possible that consumers might want to eat more seafood to follow common health claims and therefore over-report the amount of seafood eaten per week. Social desirability bias regarding pro-environmental behavior might also lead to an over-reporting of sustainable seafood consumption behavior [87][88][89]. Hence, experimental replications with actual behaviour as the dependent variable would be a valuable extension of the present research.…”
Section: Limitationsmentioning
confidence: 93%
“…The influence on the purchase is indirect. On the other hand, the eco-label's effect, as determined by Sörqvist et al (2015), can have a direct influence on the purchase of the product. For some samples (mostly fruit) it was found that respondents were more willing to buy a product with an eco-label because they thought it tasted better.…”
Section: Labelling Of Organic Productsmentioning
confidence: 99%
“…QR codes and green smartphone apps could enhance the perception of green labels for the product itself (Atkinson, 2013). Eco-labels may trigger a so-called "halo-effect" on products (Sörqvist et al, 2015). The "halo-effect" "consists of the circumstance, that several products with the FT logo are used to create the impression, that the whole product range of the manufacturer or retailer, including also large corporations, is linked with the concept and its values" (Stefańska and Nestorowicz, 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The "halo-effect" "consists of the circumstance, that several products with the FT logo are used to create the impression, that the whole product range of the manufacturer or retailer, including also large corporations, is linked with the concept and its values" (Stefańska and Nestorowicz, 2015). The "halo-effect" may increase positive perception of the product and cause positive emotions on the part of the consumer "even there is no reasonable relation between the product label and what is being evaluated about the product" (Sörqvist et al, 2015). This may also affect the buying behaviour of customers as a consequence.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%